Conflicts between Kurdistan Regional Government and Iraqi Central Government and their effects on political stability - Karim, Bryar Esmail Mhamad (2016)
Iraq is a multi-religion and multi-ethnic country, with Arabs and Kurds being the two major ethnic groups. As far as the Kurd-Arab relationship was concerned historically, it had witnessed many rebellions and uprisings. After Iraq invasion, still there were conflicts and disagreements in the relations of Iraqi central government and Kurdistan regional government within the frame of one country and in their cooperation after 2003. Conflicts between the Kurdistan regional government and Iraqi central government caused instability and threatened the unity of Iraq. While various reasons increased the conflicts between them, only a few scholars have identified the effective causes of these conflicts. But they did not explain how these causes affected the relationship of the two governments and led to the political instability. This research aims to study the relationship between Kurdistan regional government and the Iraqi central government in terms of power-sharing democracy. The objectives of the research are: to identify the causes of the conflicts between Kurdistan regional government and the Iraqi central government from 2003 to 2013 then to determine the effects of these conflicts on the political stability in Iraq. In this study, the researcher employed qualitative approach to understand the subject. Researcher collected the data by using in-depth and semi-structured interviews. The process of data analysis was based on three steps: data reduction, data display, and conclusion drawing. The findings of this study identify that the essential causes of the conflicts related to Kirkuk and oil sector. There are two levels of factors in the case of oil: Internal factors external factors of the conflict which are divided to multiple interpretations for the constitution articles, disagreement over distributing and managing the oil and intervention of foreign countries. Findings show that political process in Iraq failed to address the conflicts due to lack of consensus as well as the absence of coalition between political elites and declining of the political participation. Findings also confirm the conflicts obstructed the performance of the government and crippled the parliamentary legislation. Iraqi government fails to establish a national army. Declining legitimacy of political system that negatively affected the political stability of Iraq from 2003-2013. Extending the conflicts between two sides is a serious threat over political stability. The chaos in the absence of the application of laws would bring ethnic war between Kurd and Arab. Moreover, future research might seek for other information and data related to the research topic and complete the findings of this study which were limited to some extent by the difficult time when the data was being collected. While the scope of this study covered the period from 2003 until 2013, future study could investigate the case over a longer period for more accurate and comprehensive results. Some recommendations of this study are to rebuild the national military that would be loyal to Iraq instead of specific ethnic or sect in order to achieve political stability.